Molecular Mechanisms in Cancer - Budak, Metin; Rajkumar, Rajamanickam (IntechOpen, 2022)
Cancer is a major public health problem and much research is being conducted to develop effective treatments for various types of malignancies. In doing so, researchers must have comprehensive knowledge about what causes cancer. This book explains the mechanisms of different types of cancers in twelve chapters organized into three sections on oncogenes, tumor suppressor genes, and viral oncogenes.